2006
DOI: 10.3201/eid1204.051441
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Influenza Viruses with Resequencing Microarrays

Abstract: Resequencing microarrays rapidly identify influenza viruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
73
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 28 publications
2
73
0
Order By: Relevance
“…Among the several microarrays reported for the typing and subtyping of influenza viruses (9,13,14,19,21,22,27), a majority used at least 55 oligonucleotides as primers and detecting probes. On the other hand, the eMA influenza virus genotyping assay requires a total of 41 oligonucleotides: 16 PCR primers, 10 capture oligonucleotides, 13 bifunctional discriminator oligonucleotides, and 2 fluorescently labeled universal reporter oligonucleotides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the several microarrays reported for the typing and subtyping of influenza viruses (9,13,14,19,21,22,27), a majority used at least 55 oligonucleotides as primers and detecting probes. On the other hand, the eMA influenza virus genotyping assay requires a total of 41 oligonucleotides: 16 PCR primers, 10 capture oligonucleotides, 13 bifunctional discriminator oligonucleotides, and 2 fluorescently labeled universal reporter oligonucleotides.…”
Section: Discussionmentioning
confidence: 99%
“…However, analysis of different amplification products from multiplex RT-PCR using traditional agarose gel electrophoresis can be problematic and slow (26). Recently, different types of microarrays in combination with multiplex amplification have been reported for the typing and subtyping of influenza viruses (9,13,14,19,21,22,27).…”
mentioning
confidence: 99%
“…Microarray technologies have become a tool of choice for multiparametric diagnostic assays and for gene expression profiling (7,14,21,24). The ability to perform sensitive and reproducible microarray hybridizations depends to a great extent on the quality of the microarray substrate.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, nucleic acid microarrays have demonstrated higher sensitivity than traditional antibody-based assays, making the detection of pathogens down to 10 cfu/mL or 10 pfu/mL possible (Lin et al 2007). Indeed, several studies have shown the utility of DNA microarrays for pathogen detection (Call et al 2003a, b;Chizhikov et al 2001Chizhikov et al , 2002Davignon et al 2005;Gingeras et al 1998;Lin et al 2007;Roth et al 2004;Troesch et al 1999;Wang et al 2002Wang et al , 2003Wang et al , 2006Wilson et al 2002a, b).…”
Section: Introductionmentioning
confidence: 99%